Extraction of Fucoxanthin from Raw Macroalgae excluding Drying and Cell Wall Disruption by Liquefied Dimethyl Ether - Hideki Kanda; Yuichi Kamo; Siti Machmudah; Wahyudiono; Motonobu Goto (Marine Drugs, 2014)
Macroalgae are one of potential sources for carotenoids, such as fucoxanthin, which are consumed by humans and animals. This carotenoid has been applied in both the pharmaceutical and food industries. In this study, extraction of fucoxanthin from wet brown seaweed Undaria pinnatifida (water content was 93.2%) was carried out with a simple method using liquefied dimethyl ether (DME) as an extractant in semi-continuous flow-type system. The extraction temperature and absolute pressure were 25 °C and 0.59 MPa, respectively. The liquefied DME was passed through the extractor that filled by U. pinnatifida at different time intervals. The time of experiment was only 43 min. The amount of fucoxanthin could approach to 390 μg/g dry of wet U. pinnatifida when the amount of DME used was 286 g. Compared with ethanol Soxhlet and supercritical CO2 extraction, which includes drying and cell disruption, the result was quite high. Thus, DME extraction process appears to be a good method for fucoxanthin recovery from U. pinnatifida with improved yields.